Coupling Parameters for Modeling the Near-Field Heat Transfer Between Molecules - Sasihithlu, Karthik (Frontiers in Physics, 2021)
The behavior of near-field heat transfer between molecules at gaps which are small compared to wavelength of light is greatly influenced by non-radiative dipole-dipole interactions between the molecules. Here we derive the coupling parameters and estimate the near-field heat transfer between two molecules using coupled Drude oscillators. The predictions from this model are verified with results from standard fluctuational electrodynamics principles. The effect of orientation factor of the dipole moments in the molecules traditionally taken into consideration for analysis of resonance energy transfer between molecules but is hitherto overlooked for NFHT is also discussed.